Fingerprinting Analysis of Antioxidant Activity from Acalypa Indica using FTIR Metabolomics based on Different Extraction Methods - Amalia, Farah Marsya; Hayati, Elok Kamilah (Proceedings of the International Conference on Green Technology; Vol 15 No 1 (2025): Proceeding of 15th International Conference on Green Technology, 2026)
The A. Indica plant (Acalypha indica ) is a herbal plant that grows in tropical areas. This plant contains secondary metabolites such as alkaloids, flavonoids, steroids, triterpenoids and tannins. The aim of this research is to determine the FTIR-ATR-based secondary metabolite profile of A. Indica based on differences in extraction methods through PCA multivariate analysis and to find out what functional groups contribute actively as antioxidants to A. Indica through OPLSDA multivariate analysis. Extraction of secondary metabolites was carried out using ultrasonic, maceration and shaker methods using ethanol absolute solvent, then the method for determining antioxidant activity used was the DPPH method. The results of this study indicate that the highest yield and antioxidant content from different extraction methods were obtained using the ultrasonic method, with a yield of 6.34 grams and an antioxidant level of 140 ppm. PCA analysis showed separation of groups from various extraction methods, suggesting differences in the secondary metabolite profiles produced. Furthermore, the OPLSDA analysis identified four main functional groups acting as antioxidant compounds in the A. Indica extract using different extraction methods, namely: 1550, 1735, 1895, 830, dan 3300 cm-1. These wavenumbers correspond to the functional groups C=C aromatic , C=O stretching, C-H aromatic , and O-H stretching . These functional groups are components of quercetin, which is one of the compounds with potential antioxidant properties.